Very Late Antigen-1 Marks Functional Tumor-Resident CD8 T Cells and Correlates with Survival of Melanoma Patients - Murray, Timothy; Fuertes Marraco, Silvia A.; Baumgaertner, Petra; Bordry, Natacha; Cagnon, Laurène; Donda, Alena; Romero, Pedro; Verdeil, Grégory; Speiser, Daniel E. (Frontiers in Immunology, 2016)
A major limiting factor in the success of immunotherapy is tumor infiltration by CD8+ T cells, a process that remains poorly understood. In the present study, we characterized homing receptors expressed by human melanoma-specific CD8+ T cells. Our data reveal that P-selectin binding, and expression of the retention integrin, Very Late Antigen (VLA)-1, by vaccine-induced T cells correlate with longer patient survival. Furthermore, we demonstrate that CD8+VLA-1+ tumor-infiltrating lymphocytes (TIL) are highly enriched in melanoma metastases in diverse tissues. VLA-1-expressing TIL frequently coexpress CD69 and CD103, indicating tissue resident memory cell (TRM) differentiation. We employed a mouse model of melanoma to further characterize VLA-1-expressing TIL. Our data show that VLA-1+ TRM develop in murine tumors within 2 weeks, where they exhibit increased activation status, as well as superior effector functions. In addition, in vivo blockade of either VLA-1 or CD103 significantly impaired control of subcutaneous tumors. Together, our data indicate that VLA-1+ TRM develop in tumors and play an important role in tumor immunity, presenting novel targets for the optimization of cancer immunotherapy.